Nordic perspectives on disability studies in education: a review of research in Finland and Iceland - Katariina Hakala; Kristín Björnsdóttir; Sirpa Lappalainen; Ingólfur Ásgeir Jóhannesson; Antti Teittinen (Education Inquiry, 2018)
Disability studies in education (DSE) is an interdisciplinary field derived from the need to re-conceptualise special education dominated by a medical perspective on disability. In this article we identify what characterises DSE research and consider whether there is a case for arguing for a specific field of DSE in Finland and Iceland. Our analysis is based on a review of 59 studies published by Finnish and Icelandic scholars during the time period of ratification process of the UN Convention on the Rights of People with Disabilities from 2007 to 2016 in Finland and Iceland. We suggest that DSE has emerged as a dynamic area of research in both countries. It has provoked researchers to analyse disability in social contexts and turn the gaze from individual person with disabilities to the social structures and educational policies and practices. The fields of DSE in Finland and Iceland have not developed in identical ways and both have fluid crossovers to related fields such as disability studies and inclusive education. We argue for the potential of DSE to contribute to the discussion on educational equality and social justice. However, this requires opportunities to bring together scholars across disciplinary borders.